Patient‐Clinician Discordance in Perceptions of Treatment Risks and Benefits in Older Patients with Acute Myeloid Leukemia. (23rd August 2018) - El‐Jawahri, Areej; Nelson‐Lowe, Margaret; VanDusen, Harry; Traeger, Lara; Abel, Gregory A.; Greer, Joseph A.; Fathi, Amir; Steensma, David P.; LeBlanc, Thomas W.; Li, Zhigang; DeAngelo, Daniel; Wadleigh, Martha; et al.
Abstract: Background: Older patients (≥60 years) with acute myeloid leukemia (AML) face difficult decisions regarding treatment with "intensive" chemotherapy that carries significant toxicity for a small chance of a cure versus "nonintensive" chemotherapy to control the disease, but with fewer side effects. However, studies of how these patients understand the risks and benefits of such treatments are lacking. Methods: We conducted a longitudinal study of older patients newly diagnosed with AML assessing patients' ( n = 100) and oncologists' ( n = 11) perceptions of treatment‐related mortality at enrollment and prognosis at 1 month. We examined concordance between patients' and oncologists' perceptions using Cohen's kappa (κ < 0.10 indicates little/no concordance). Results: We enrolled patients within 72 hours of initiating intensive ( n = 50) or nonintensive ( n = 50) chemotherapy. Whereas 91% of patients reported that they were "somewhat" to "extremely likely" to die from treatment, oncologists estimated that only 12% were at high risk of dying because of treatment (κ = −0.09). Ninety percent of patients reported that they were "somewhat" or "very likely" to be cured of their AML, whereas oncologists estimated this chance of cure for only 31% of patients (κ = 0.05). Among patients receiving intensive chemotherapy, 98% reported that they were "somewhat" or "very likely" to be cured, whereas their oncologists estimated this likelihood of cure for only 49% (κ = 0.04); among those receiving nonintensive chemotherapy and their clinicians, these proportions were 82% and 13%, respectively (κ = 0.03). Patients who indicated a lower likelihood of cure reported significantly higher depression symptoms ( p = .03). Conclusion: Older patients with AML overestimate the risks and benefits of treatment. Interventions to facilitate communication and enhance patients' understanding of the goals of therapy and treatment risk are needed. Implications for Practice: Older patients with acute myeloid leukemia (AML) are confronted with challenging decisions regarding treatment with "intensive" chemotherapy that carries significant toxicity for a small chance of a cure versus "nonintensive" chemotherapy to control the disease, but with fewer side effects. A clear understanding of the likely outcome and risks of the various treatment strategies is essential for these patients to make informed decisions about their care. This article reports that older patients with AML overestimate both the risks and benefits of treatment and have substantial misperceptions about their prognosis. Interventions to enhance patients' understanding of their prognosis and treatment risk are needed. Abstract : Acute myeloid leukemia (AML) in adults aged 60 years and older has a poor prognosis. The goal of this study was to describe the perceptions of older patients with AML regarding treatment decisions and the potential risks and benefits of treatment. Patient‐clinician concordance in estimated treatment risk and the likelihood of cure with intensive and nonintensive treatment was also examined.